2019
DOI: 10.3390/su11082418
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Development as a Driver of Economic Growth: Evidence from Multivariate Panel Data Analysis

Abstract: Renewable energy is being increasingly touted as the “fuel of the future,” which will help to reconcile the prerogatives of high economic growth and an economically friendly development trajectory. This paper seeks to examine relationships between renewable energy production and economic growth and the differential impact on both developed and developing economies. We employed the Fully Modified Ordinary Least Square (FMOLS) regression model to a sample of 20 developed and developing countries for the period 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 60 publications
1
46
0
1
Order By: Relevance
“…The uncertain context of Brexit creates more barriers. Germany made big progress in the consumption of fossil and nuclear fuels, while France and Italy have serious problems in meeting the targets for 2020 [64][65][66][67][68][69]. Netherlands also encountered difficulties because its final energy consumption is based on a natural gas network that is quite cheap; government subsidies for the RES promotion are not attractive, being lower than in Scandinavian countries.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertain context of Brexit creates more barriers. Germany made big progress in the consumption of fossil and nuclear fuels, while France and Italy have serious problems in meeting the targets for 2020 [64][65][66][67][68][69]. Netherlands also encountered difficulties because its final energy consumption is based on a natural gas network that is quite cheap; government subsidies for the RES promotion are not attractive, being lower than in Scandinavian countries.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable we used in model 1 is the change in the lognormal values of GDP per capita. Thus, Singh et al [29] emphasized that, the existing literature focused exclusively on GDP per capita as an indicator of economic growth. It was estimated that the internet economy in the G-20 countries will double between 2012 and 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their conclusions indicate that effective policy interventions should ensure that objectives are orientated towards the long term with the aim of reducing the risks perceived by financial institutions in funding biomass producers. Based on a Fully Modified Ordinary Least Square (FMOLS) regression model analysis, Singh et al [26] argue that renewable energy production is associated with a positive and statistically significant impact on economic growth in both developed and developing countries for the period 1995-2016. Starting with the analysis based on a Malaysian Case Study, Takeda et al [27] showed that electricity from renewables has greater adverse impact on workers from the supply chain than the conventional electricity mix, in view of the social aspects countered.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%